(untitled) (Diversity Research: Journal of Analysis and Trends, 2023)
the article reflects on the importance of mastering the pedagogical resources of the Vangi ideology, in which the main pedagogical and political resources and the ideas of the new ideology in our pedagogical heritage are interpreted.